2004
DOI: 10.1097/01.ico.0000114121.05360.19
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Quantification of Calcified Corneal Lesions With Optical Coherence Tomography

Abstract: Noncontact slit-lamp-adapted OCT may be of value in assessing calcified corneal lesions. Corneal OCT could also be used to precisely measure the depth of these corneal processes and evaluate treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
3
17
0
Order By: Relevance
“…The reflected optical delay signals were transformed into geometric values using the instrument-specific calibration factor and the group refractive index of the cornea of 1.389 (at 1310 nm). 10,11 Transparency testing…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The reflected optical delay signals were transformed into geometric values using the instrument-specific calibration factor and the group refractive index of the cornea of 1.389 (at 1310 nm). 10,11 Transparency testing…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The central and paracentral cornea was examined with a clinical slit lamp-adapted OCT system (Heidelberg Engineering, Heidelberg, Germany) [3][4][5][6][7][8][9][10] . The principle of OCT is based on low-coherence interferometry having as light source a superluminescent diode (SLD-561; Superlum, Moscow, Russian Federation) operating at a wavelength of l = 1310 nm, with a bandwidth of 20 nm and an intensity of the incident light of less than 200 mW.…”
Section: Corneal Octmentioning
confidence: 99%
“…[1][2][3] Recently, the interferometric-based method of slit lamp-adapted optical coherence tomography (OCT) has gained importance to image the cornea and anterior eye segment. 3,4 This noncontact and high-resolution imaging method was used to measure the central CT, 3 the epithelium, 5 and various corneal diseases 6,7 and in particular to assess the changes after photorefractive keratectomy 8 or laser in situ keratomileusis. 9 Previous method comparison studies confirmed a high reproducibility and accuracy of central CT measurements with slit lamp-adapted OCT compared with ultrasound (US) pachymetry.…”
mentioning
confidence: 99%
“…14 Retroiridian structures remained obscured because the pigment epithelium and the stroma of the iris caused severe backscattering and absorption.…”
Section: Resultsmentioning
confidence: 99%